On N-prime ideals - (:unkn) unknown (Politechnica University of Bucharest, 2018)
In this article, we introduce an intermediate classes of ideals between prime and quasi primary ideals, denoted by R-prime, and we focus on some properties of R-prime ideals. Moreover, we defined a topology on the set of all R-prime ideals such that we examine the topological concepts, irreducibility, connectedness, and seperation axioms. © 2018 Politechnica University of Bucharest. All rights reserved.
Keywords: Prime ideals; Prime spectrum; R-prime ideals; R-prime spectrum